Hrywda - Rodziewiczowna, Maria, 1863-1944. (Warszawa : Wydawnictwa ALFA, 1992)
This tale is set in a backward Belarus village, describing a gloomy picture of life.
Keywords: Belarus -- Rural conditions -- Fiction